Art therapy to improve quality of life of cancer patients and their carers in Bangladesh - Dowla, Rumana; Goodman, Annekathryn; Kashem, Tahsin (Scientific Research, 2022)
This article was published in the Journal of Cancer Therapy [Copyright © 2019 by author(s) and Scientific Research Publishing Inc. This work is licensed under the Creative Commons Attribution International License (CC BY 4.0). and the definite version is available at: http://dx.doi.org/10.4236/jct.2019.106038 The Journal's website is at: https://www.scirp.org/journal/paperinformation.aspx?paperid=93189